Pre‐oxygenation with facemask oxygen vs high‐flow nasal oxygen vs high‐flow nasal oxygen plus mouthpiece: a randomised controlled trial. (17th August 2021) - Lyons, C.; McElwain, J.; Coughlan, M. G.; O'Gorman, D. A.; Harte, B. H.; Kinirons, B.; Laffey, J. G.; Callaghan, M.
Summary: High‐flow nasal oxygen used before and during apnoea prolongs time to desaturation at induction of anaesthesia. It is unclear how much oxygenation before apnoea prolongs this time. We randomly allocated 84 participants to 3 minutes of pre‐oxygenation by one of three methods: 15 l.min ‐1 by facemask; 50 l.min ‐1 by high‐flow nasal cannulae only; or 50 l.min ‐1 by high‐flow nasal cannulae plus 15 l.min ‐1 by mouthpiece. We then anaesthetised and intubated the trachea of 79 participants and waited for oxygen saturation to fall to 92%. Median (IQR [range]) times to desaturate to 92% after pre‐oxygenation with facemask oxygen, high‐flow nasal oxygen only and high‐flow nasal oxygen with mouthpiece, were: 309 (208‐417 [107‐544]) s; 344 (250‐393 [194‐585]) s; and 386 (328‐498 [182‐852]) s, respectively, p = 0.014. Time to desaturation after facemask pre‐oxygenation was shorter than after combined nasal and mouthpiece pre‐oxygenation, p = 0.006. We could not statistically distinguish high‐flow nasal oxygen without mouthpiece from the other two groups for this outcome. Median (IQR [range]) arterial oxygen partial pressure after 3 minutes of pre‐oxygenation by facemask, nasal cannulae and nasal cannulae plus mouthpiece, was: 49 (36‐61 [24‐66]) kPa; 57 (48‐62 [30‐69]) kPa; and 61 (55‐64 [36‐72]) kPa, respectively, p = 0.003. Oxygen partial pressure after 3 minutes of pre‐oxygenation with nasal and mouthpiece combination was greater than after facemask pre‐oxygenation, p = 0.002, and after high‐flow nasal oxygen alone, p = 0.016. We did not reject the null hypothesis for the pairwise comparison of facemask pre‐oxygenation and high‐flow nasal pre‐oxygenation, p = 0.14.